Theoretical and Practical Aspects and Indicators of Financial Security of Enterprises - Mamatkulova, Nadira (International Journal of Psychosocial Rehabilitation, 2020)
This article explores the theoretical and practical aspects of the financial security of enterprises by studying the experience of scientists from Uzbekistan and foreign countries. It also analyzes the financial security of industrial enterprises operating in the country, and develops scientific proposals and practical recommendations for financial security. Index Terms— Equity, Enterprises, Ensuring Financial Security of an Enterprise, Financial Security, Financial Margin, Increase in the Share of Liquid Assets in Gross Assets, Financial Resources, Financial Risk, Financial Indicators, “Bekabadcement” JSC, Liquidity, Rate of Return.